The Severe Heterogeneous Asthma Research collaboration, Patient-centred (SHARP) ERS Clinical Research Collaboration: a new dawn in asthma research. Issue 5 (29th November 2018) - Djukanovic, Ratko; Adcock, Ian M.; Anderson, Gary; Bel, Elisabeth H.; Canonica, Giorgio W.; Cao, Hui; Chung, Kian Fan; Davies, Donna E.; Genton, Céline; Gibson-Latimer, Toni; Hamerlijnck, Dominique; Heuvelin, Elise; et al.
The past 30 years have seen major advances in the understanding of asthma mechanisms and the clinical introduction of effective medicines based on these pathways. The first major step-change occurred in the 1980s with the development of bronchial challenge as a research tool to dissect the airways inflammatory responses [1, 2]. The advent of bronchoscopy and sputum induction in the early 1990s, to study asthma pathology in vivo, enabled the description of characteristic features of airways inflammation and remodelling [3–6], while epidemiological and challenge studies showed viruses to be the main cause of asthma exacerbations [7, 8]. One of the greatest discoveries was the central role of Type-2 cytokines driven by the interleukin (IL)-4/IL-13 and IL-5 pathways, for which simple biomarkers, like sputum eosinophils and exhaled nitric oxide, were discovered [9, 10]. However, it was not until early 2000s that the basic science translated into fundamentally novel treatments, beginning the "era of biological treatments" with the anti-IgE antibody, omalizumab [11]. It took almost 15 years for the next biologics to arrive, targeting the pro-eosinophilic cytokine IL-5, showing how difficult drug development can be [12, 13]. SHARP (Severe Heterogeneous Asthma Research collaboration, Patient-centred) is set up to harmonise severe asthma management across Europe and unravel the heterogeneity of severe asthma in a patient-centred way http://ow.ly/s1x730mwLpk